Socio-informatica giuridica tra Europa e Giustizia (Società e diritti, 2022)
AbstractThe author, in dealing with the issues of modern law, which run through the same magazine Society and Rights, proposes to use a new science: called socio-legal informatics. The revolution of the society of information - led by English-speaking multinational companies - will change the context of the application and interpretation of the law. It is necessary to analyse the capacity of jurists to dictate the material and symbolic conditions that will enable information technology to change the legal system and accelerate change in this area as well.